Microbial population responses to pH and salt shock during phenols degradation under high salt conditions revealed by RISA and AFDRA. - Yan, Bin (Water Science and Technology)
The responses of microbial community to pH and salt shock during phenols degradation under high salt conditions were revealed by two DNA fingerprint methods, i.e. ribosomal intergenic spacer analysis (RISA) and amplified functional DNA restriction analysis (AFDRA), together with 16S rDNA clone library analysis. It was shown that the phenols removal rate was improved with increasing NaCl concentration from 0 to 50 mg/L, and could remain at a high level even in the presence of 100 mg/L NaCl. The degradation efficiency remained stable under neutral conditions (pH 7.0?9.0), but decreased sharply under acidic (below pH 5.0) or more alkaline conditions (above pH 10.0). The community structure was dramatically changed during salt fluctuations, with Halomonas sp. and Marinobacter sp. as the predominant salt-tolerant species. Meanwhile, Marinobacter sp. and Alcaligenes faecalis sp. were the major species which might play the key role for stabilizing the treatment systems under different pH conditions. Moreover, the changes of phenol hydroxylase genes were analyzed by AFDRA, which showed that these functional genes were substantially different under any shock conditions.